2018
DOI: 10.1167/18.3.20
|View full text |Cite
|
Sign up to set email alerts
|

Both saccadic and manual responses in the amblyopic eye of strabismics are irreducibly delayed

Abstract: Abnormal early visual development can result in a constellation of neural and visual deficits collectively known as amblyopia. Among the many deficits, a common finding is that both saccadic and manual reaction times to targets presented to the amblyopic eye are substantially delayed when compared to the fellow eye or to normal eyes. Given the well-known deficits in contrast sensitivity in the amblyopic eye, a natural question is whether the prolonged reaction times are simply a consequence of reduced stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…At the moment there are no data available linking changes in attentional processing with treatment outcomes in strabismic amblyopia. Several recent lines of research point to temporal processing delays in the strabismic amblyopic eye relative to the fellow eye . Is it possible that increased retinal contrast from optical correction reduces the latency of neuronal responses in the strabismic eye, bringing the two eyes into better temporal correspondence?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment there are no data available linking changes in attentional processing with treatment outcomes in strabismic amblyopia. Several recent lines of research point to temporal processing delays in the strabismic amblyopic eye relative to the fellow eye . Is it possible that increased retinal contrast from optical correction reduces the latency of neuronal responses in the strabismic eye, bringing the two eyes into better temporal correspondence?…”
mentioning
confidence: 99%
“…This seems unlikely; the temporal delays in strabismic amblyopic eyes persist when stimulus contrast is varied 21 and when resolution and contrast deficits associated with the amblyopia are accounted for. 22 Regardless of the mechanism behind optical treatment of strabismic amblyopia, the fact that considerable gains in acuity and stereopsis 23,24 can be achieved places optometrists at the frontline of treatment. A useful field guide, informed by sound empirical evidence, has been complied by Chen and Cotter.…”
mentioning
confidence: 99%
“…Although three of our strabismic amblyopes (No. 3,4, and 8) manifested small anisometropia, we decided not to create a third group of participants with mixed type of amblyopia and to classify subjects with strabismus as only strabismic amblyopes, irrespectively of their refractive status (Gambacorta et al, 2018). The clinical characteristics of strabismic as well as anisometropic individuals is presented in Table 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it seems that the stimulus attributes (e.g., luminance, contrast) should not account for this discrepancy. Interestingly, Gambacorta et al (2018) showed that for some amblyopes (especially strabismic), saccadic latencies were increased, even when the signal strength in the two eyes was equated. Thus, future research on a larger group of amblyopic subjects is needed to further explore the source of difference in saccadic latency between the strabismic and anisometropic amblyopes.…”
Section: Saccadic Latency In Amblyopiamentioning
confidence: 99%
See 1 more Smart Citation